Global Regulation by gidA in Pseudomonas syringae - Kinscherf, Thomas G. (American Society for Microbiology, 2002)
Analysis of two virulence mutants of Pseudomonas syringae B728a revealed that the Tn 5 sites of insertion were within the gidA open reading frame (ORF). These mutations were pleiotropic, affecting diverse phenotypic traits, such as lipodepsipeptide (syringomycin and syringopeptin) antibiotic production, swarming, presence of fluorescent pigment, and virulence. Site-specific recombination of a disrupted gidA gene into the chromosome resulted in the same phenotypic pattern as transposon insertion. Mutant phenotypes were restored by the gidA ORF on a plasmid. The salA gene, a copy number suppressor of the syringomycin-deficient phenotype in gacS and gacA mutants, was also found to suppress the antibiotic-negative phenotypes of gidA mutants, suggesting that gidA might play some role in salA regulation. Reporter studies with chromosomal salA-lacZ translational fusions confirmed that salA reporter expression decreased approximately fivefold in a gidA mutant background, with a concurrent decrease in the expression of the syringomycin biosynthetic reporter fusion syrB-lacZ. Wild-type levels of reporter expression were restored by supplying an intact gidA gene on a plasmid. Often described as being involved in cell division, more recent evidence suggests a role for gidA in moderating translational fidelity, suggesting a mechanism by which global regulation might occur. The gidA gene is essentially universal in the domains Bacteria and Eucarya but has no counterparts in Archaea, probably reflecting specific differences in the translational machinery between the former and latter domains.